Vibration-based structural health monitoring of a wind turbine incorporating environmental and operational conditions - Hanbay, Serap. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Structural health monitoring of wind turbines has become important in recent years in order to detect any damage in such structures at its early stage and avoid sudden collapse. Modal parameters which represent the dynamic behaviour of a structure are obtained to track any change in these parameters, which might be the sign of a damage in the structure. However, environmental and operational conditions have also e ects on modal parameters of wind turbines besides of damage. In this study, structural health monitoring of a 900 kW onshore wind turbine incorporating environmental and operational conditions was performed. The band range of change in modal parameters due to environmental and operational conditions was determined. Firstly, modal identi cation of the wind turbine was done using Enhanced Frequency Domain Decomposition method using 1-year monitoring data obtained from accelerometers placed on the turbine. Then, the e ects of wind speed, rotor speed, temperature and nacelle position on the dynamic behaviour of the wind turbine were evaluated. Lastly, a nite element model of the turbine with global springs at the base representing the behaviour of soil and piles were developed in SAP2000 software and veri ed with identi ed modal values. In conclusion, it was shown that there were signi cant variations in modal parameters due to both environmental and operational conditions. However, when these e ects were removed, there was a consistency in frequency values. Also, the nite element model with global springs ensured that the modal parameters obtained from the nite element model and in-situ measurements were matching well.
Keywords: Structural health monitoring.; Wind turbines.